LEGAL STUDY OF INFORMED CONSENT LAW RELATED TO RIGHTS AND OBLIGATIONS FOR PATIENTS AND DOCTORS FROM THE ASPECT OF LAW NUMBER 17 OF 2023 CONCERNING HEALTH - Wahyu Rahmatika; T. Riza Zarzani; Sumarno, Sumarno (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Informed consent is essentially a communication process between a doctor and a patient regarding an agreement on medical procedures to be performed on the patient. The information provided by the doctor serves as the basis for the patient to give consent. This informed consent can also be a reason for a lawsuit against the doctor if there is a deviation in the doctor's practice. And for the doctor himself, it also serves as documentary evidence that can be accounted for if there is a claim in the future. Regarding informed consent, everything is regulated in detail in Law Number 17 of 2023 concerning Health. The implementation of this law has the potential to improve the quality of communication between doctors and patients, standardize informed consent procedures, and increase public health literacy. This study uses normative legal research, namely research that focuses on literature studies of laws and regulations, doctrines, and legal principles from primary, secondary, and tertiary legal materials with a qualitative descriptive analytical research method.